Acquired Hemophilia A Presenting as Intramuscular Hematoma - Ghassan Al-Shbool MD; Anusha Vakiti MD (SAGE Publishing, 2018)
Acquired hemophilia A poses a clinical and diagnostic challenge. Although rare, it is still the most common acquired factor deficiency. We present a case of acquired hemophilia A diagnosed in a 71-year-old female who presented with a right thigh hematoma of acute onset. The diagnosis was established based on the coagulation profile along with factor VIII levels, mixing studies, and inhibitor levels. The patient received multiple lines of therapy including steroids, factor VIIa, Obizur (porcine-derived recombinant factor VIII), followed by multiple cycles of chemotherapy including cyclophosphamide and rituximab.